Physical Kinetics of Loop Quantum Gravity and Blackhole Dynamics: Kinetic Theory of Quantum Spacetime, Blackhole Phase Transition Theory and Blackhole Fission. - Kabe, Koustubh (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In the following chapter, a sincere endeavor is made to build a physically as well as in most later aspects a mathematically simple but rigorous physical kinetics of spacetime and of blackholes. Starting with a 3-volume quantization result of the now standard Ashtekar-Lewandowski Quantum Riemannian Geometry, and based on the work of the author on time as a vortex, a 4-volume spacetime quantum, a rapidly fluctuating one is developed and the foundations seem to look shaky in the very beginning, but start to get stronger and stronger as one starts to enter the end of the section on the physical kinetics of blackholes. Thus, experimental tests and observational predictions have been made whenever seem required or appropriate for justification, examples from laboratory table-top physics provided. Once the framework of kinetic theory has been developed, the author has entered into the realm of blackhole phase transitions nucleating from backgroung spacetime as well as other blackhole phase transitions. The equations of phase transitions have been rigorously analyzed and physical interpretations and physical predictions provided. Also certain the Bardeen-Carter-Hawking standard zeroeth law of blackhole dynamics been deduced in the context of equilibrium phase transitions in blackholes. The possibility of splitting of the Kerr-Newman blackhole akin to nuclear fission is obtained. An interesting work is the conception and extensin of the stretched horizon which was constructed by Ashoke Sen in the context of unphysical extremal blackholes in string theory -to that of isolated horizons in the context of arbitrary blackholes as proposed by Rovelli . Quantum gravitational dispersion as well as diffraction of light and gravitational waves by discrete nature of quantum spacetime geometry has been predicted in phenomenology. The paper predicts the gravi-electric Meissner effect in the wake of the Galilean superconductivity in the form of locally Lorentzian spacetimes as a critical behavior in the context of a second order phase transition. The property of the blackholes to undergo fission is demonstrated in the equations of phase transitions. This is used to explain the astrophysical phenomenon of Quasars. An iso-Higgs multiplet is qualitatively predicted as basic constituents of the blackhole. A liquid droplet model is suggested to explain the newly predicted phenomenon of blackhole fission in this paper.The chapter as a whole builds the foundations of the subject of the title of the paper.